Martensolasma jocheni, a new genus and species of harvestman from Mexico (Opiliones: Nemastomatidae: Ortholasmatinae) - Shear, William A. (Zootaxa, 2006)
Martensolasma jocheni n. g., n. sp. is described from the Mexican State of Aguascalientes. The new genus is distinct from Dendrolasma Banks and Ortholasma Banks in lacking the extensive modifications of the eye tubercle.